2018
DOI: 10.1002/ange.201808818
|View full text |Cite|
|
Sign up to set email alerts
|

Operando X‐Ray Absorption Spectroscopy Shows Iron Oxidation Is Concurrent with Oxygen Evolution in Cobalt–Iron (Oxy)hydroxide Electrocatalysts

Abstract: Iron cations are essential for the high activity of nickel and cobalt-based (oxy)hydroxides for the oxygen evolution reaction, but the role of iron in the catalytic mechanism remains under active investigation. Operando Xray absorption spectroscopya nd density functional theory calculations are used to demonstrate partial Fe oxidation and ashortening of the FeÀObond length during oxygen evolution on Co(Fe)O x H y .C obalt oxidation during oxygen evolution is only observed in the absence of iron. These results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 41 publications
2
39
2
Order By: Relevance
“…9 The nickel oxyhydroxide has been investigated as an active phase for OER 45,46 and the iron oxyhydroxide possibly plays a crucial role. 47 Nevertheless, while the iron peak is surely masked because of the OER, the nickel oxidation (considered vital for high OER performance) can be experimentally detected and thus, studied by means of CVs. [48][49][50] Keeping this in mind, Luan et al studied the proton diffusion coefficient during Ni(OH) 2 oxidation that can be estimated for diffusionlimited reactions using the Randles-Sevcik equation.…”
Section: Resultsmentioning
confidence: 99%
“…9 The nickel oxyhydroxide has been investigated as an active phase for OER 45,46 and the iron oxyhydroxide possibly plays a crucial role. 47 Nevertheless, while the iron peak is surely masked because of the OER, the nickel oxidation (considered vital for high OER performance) can be experimentally detected and thus, studied by means of CVs. [48][49][50] Keeping this in mind, Luan et al studied the proton diffusion coefficient during Ni(OH) 2 oxidation that can be estimated for diffusionlimited reactions using the Randles-Sevcik equation.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that the OER active phase of CFCO catalysts comprises aggregates of randomly stacked (Co, Fe)OOH nanosheets. Thus, the amorphous Fe-modyfied cobalt oxyhydroxides derived from Brownmillerite-type CFCO are promising OER catalysts with good electrocatalytic activity and long-term durability under strongly alkaline conditions.The in situ formation of an OER electrocatalytically active CoOOH phase has been also reported in other systems [32][33][34][35][36][37][38][39][40][41]. Zhou et al reported that catalysts based on the simple Prussian blue analog NaxCoFe(CN)6 form a CoOOH active phase with the replacement of oxygen vacancies by the hydroxyl groups driven by an applied electric field 32.…”
mentioning
confidence: 77%
“…34 In this case, the active phase has been assigned to γ-CoOOH clusters embedded in phosphate glass matrices by Yoshida et al 35 Enman et al found that Fe species in CoOOH avoid the oxidation of Co spices and proposed the different OER mechanism in CoOOH and Fe-doped CoOOH. 36 Most of the above-mentioned studies show that catalyst might undergo modification through clusters formation and/or surface modification under standard OER conditions. Herein, we extended the durability studies to one month leading to polarization of the catalyst with total electric charge of the order of ∽10 5 C cm -2 .…”
Section: Discussionmentioning
confidence: 99%
“… 616 Moreover, the further oxidation of Fe 3+ species to a higher oxidation state was described, implying a high electrochemical activity of these sites. 617 , 618 …”
Section: Examplesmentioning
confidence: 99%